Building communities: a history of the eruv in America - Mintz, Adam (North American Jewish studies, 2023)
"Jewish law forbids carrying objects between private or public areas on the Sabbath. However, rabbinic authorities deemed carrying permissible within a physical enclosure called an eruv. This book explores the rabbinic debates surrounding the creation of such enclosures in North American cities and examines the evolution of American Orthodox communities from the late-nineteenth century through the 1960s"--